2022
DOI: 10.1590/1806-9282.20211348
|View full text |Cite
|
Sign up to set email alerts
|

Serum Prealbumin: a potential predictor of Right Ventricular Dysfunction in patients receiving programmed hemodialysis

Abstract: OBJECTIVE: Prealbumin has been a reliable marker to predict protein energy malnutrition and hypercatabolic state. In this analysis, we particularly aimed to investigate the potential association between serum prealbumin levels and right ventricular dysfunction in patients receiving programmed hemodialysis. METHODS: A total of 57 subjects were included in the analysis. The subjects were then categorized into two groups: right ventricular dysfunction (n=18) and non-right ventricular dysfunction (n=39) groups. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In addition to the above-mentioned findings, the predictive value of prealbumin for cardiac disease has also been reported. Investigators have demonstrated strong relationships between low prealbumin and angiographic severity, [8] in-hospital MACE [30] in ACS patients, poor outcome in acute HF patients, [31,32] and right ventricular dysfunction in hemodialysis patients. [33] In agreement with Wang, et al [30] our results showed that low prealbumin was independently correlated with increased inhospital MACE in patient with STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above-mentioned findings, the predictive value of prealbumin for cardiac disease has also been reported. Investigators have demonstrated strong relationships between low prealbumin and angiographic severity, [8] in-hospital MACE [30] in ACS patients, poor outcome in acute HF patients, [31,32] and right ventricular dysfunction in hemodialysis patients. [33] In agreement with Wang, et al [30] our results showed that low prealbumin was independently correlated with increased inhospital MACE in patient with STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…First, as described in Table 1 of that study 1 , C-reactive protein (CRP) was higher in patients with RVD compared with patients without RVD [1.45 (0.95–3.30) versus 0.80 (0.40–1.60), p=0.023], suggesting that both prealbumin and CRP concentrations had a significant difference in patients with and without RVD. In this case, either lower prealbumin or elevated CRP concentrations may be associated with poorer right ventricular function, and it cannot be roughly assumed that lower right ventricular function is only associated with lower prealbumin, ignoring the role of CRP.…”
mentioning
confidence: 89%
“…We read with great interest a recent study 1 investigating the relationship between serum prealbumin concentration and right ventricular dysfunction (RVD) in patients undergoing programmed hemodialysis. In this study 1 , the results found that patients with RVD had lower prealbumin concentration compared with patients without RVD (23.83±8.50 mg/dL versus 31.38±6.81 mg/dL, p=0.001), and prealbumin concentration had an important role in predicting RVD. However, after reading this study carefully, we think that the following questions deserve further clarification.…”
mentioning
confidence: 99%